PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA REALISTIK DALAM PERKULIAHAN PENGEMBANGAN PEMBELAJARAN MATEMATIKA SEKOLAH DASAR DI PGSD TEGAL - Andrijati, Noening (Jurnal Penelitian Pendidikan, 2012)
The aim of this research is to improve the quality of lectures of the development of elementary shool mathematics learning, especially the material of realistic mathematics approach, through the development of its learning equipment based on modeling the way strategy. This research approach is action research conducted in two cycles. Data were collected through observation and testing techniques. The criteria of success in this study is average formative test scores of students over 70, classical mastery learning score at least 75%, students learning activities scores and lecturers performance scores least 70.5 (B). After development of learning equipment for realistic mathematics using modeling the way strategy, the average formative score test was 72.4 and the classical mastery learning score was 56% in first cycle. In second cycle, the average formative score test was 76.4 and the classical mastery learning score was 80%. Student learning activities score in the first cycle was 78.75 (B) and in the second cycle it increased to 86.25 (A). Lecturers performance score in first cycle was 81.25 (AB), and in second cycle it increased to 90 (A). These results were considered to be sufficient, because the students’ achievement and learning activities as well as the lecturers’ performance have met the success criteria. Thus, it can be concluded that the development of realistic mathematics learning using strategy of modeling the way can improve the quality of development of elementary school mathematics learning at the Department of Elementary School Teacher Training Tegal.